The three‐finger toxin fold: a multifunctional structural scaffold able to modulate cholinergic functions. (21st March 2017) - Kessler, Pascal; Marchot, Pascale; Silva, Marcela; Servent, Denis
Abstract: Three‐finger fold toxins are miniproteins frequently found in Elapidae snake venoms. This fold is characterized by three distinct loops rich in β‐strands and emerging from a dense, globular core reticulated by four highly conserved disulfide bridges. The number and diversity of receptors, channels, and enzymes identified as targets of three‐finger fold toxins is increasing continuously. Such manifold diversity highlights the specific adaptability of this fold for generating pleiotropic functions. Although this toxin superfamily disturbs many biological functions by interacting with a large diversity of molecular targets, the most significant target is the cholinergic system. By blocking the activity of the nicotinic and muscarinic acetylcholine receptors or by inhibiting the enzyme acetylcholinesterase, three‐finger fold toxins interfere most drastically with neuromuscular junction functioning. Several of these toxins have become powerful pharmacological tools for studying the function and structure of their molecular targets. Most importantly, since dysfunction of these receptors/enzyme is involved in many diseases, exploiting the three‐finger scaffold to create novel, highly specific therapeutic agents may represent a major future endeavor. This is an article for the  special issue XVth International Symposium on Cholinergic Mechanisms . Abstract : We provide a detailed description of the three‐finger fold proteins, their structure, diversity, and functional roles. The molecular interaction of three‐finger toxins with cholinergic targets and the engineering of this multipotent scaffold are particularly emphasized. This is an article for the  special issue XVth International Symposium on Cholinergic Mechanisms .